2013
DOI: 10.1002/ajmg.a.36118
|View full text |Cite
|
Sign up to set email alerts
|

Risk and protective factors in the origin of conotruncal defects of heart—a population‐based case–control study

Abstract: Congenital heart defect (CHD) cases have been evaluated together as a group in some previous epidemiological studies. However, different CHD entities have different etiologies, and the underlying causes are unclear in the vast majority of patients. Thus the aim of this study was to analyze the possible association of different maternal diseases with the risk of four types of conotruncal defects (CTD), that is, truncus arteriosus, d-transposition of the great arteries, tetralogy of Fallot, and double-outlet rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 58 publications
(60 reference statements)
0
20
0
Order By: Relevance
“…A possible protective effect of folic acid supplements on CHDs is, however, controversial. While some studies have reported reduced risk of CHDs in children whose mothers have taken multivitamins with folic acid or pure folic acid supplements, or after folic acid food fortification, other studies have reported no effect on CHDs of folic acid food fortification …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible protective effect of folic acid supplements on CHDs is, however, controversial. While some studies have reported reduced risk of CHDs in children whose mothers have taken multivitamins with folic acid or pure folic acid supplements, or after folic acid food fortification, other studies have reported no effect on CHDs of folic acid food fortification …”
Section: Introductionmentioning
confidence: 99%
“…10 A possible protective effect of folic acid supplements on CHDs is, however, controversial. While some studies have reported reduced risk of CHDs in children whose mothers have taken multivitamins with folic acid 11,12 or pure folic acid supplements, 13,14 or after folic acid food fortification, 6 other studies have reported no effect on CHDs of folic acid food fortification. 15,16 In the Medical Birth Registry of Norway, information on the use of folic acid and multivitamin supplements has been recorded for all women giving birth since 1999.…”
Section: Introductionmentioning
confidence: 99%
“…42,43 All of these modifiable risk factors should be addressed with potential mothers before conception to minimize risk to the fetus.…”
Section: Environmental Risk Factorsmentioning
confidence: 99%
“…During embryonic development, the abnormity of outflow tract (OFT) morphogenesis, stemming from altered migration and development of the arterial heart field and second heart field (AHF/SHF), is considered to be responsible to CTDs . The causes of sporadic CTD include multiple cardiac development gene variants, altered genetic buffering pathways, maternal disease, and environmental factors . The genetic basis of CHD, including CTDs, has been partially studied in former studies.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 The causes of sporadic CTD include multiple cardiac development gene variants, altered genetic buffering pathways, maternal disease, and environmental factors. 5 The genetic basis of CHD, including CTDs, has been partially studied in former studies. CTDs exist among several syndromic diseases along with extracardiac symptoms and 22q11.2 deletion syndrome is a notable one.…”
Section: Introductionmentioning
confidence: 99%